Detection and analysis of morphotectonic features utilizing SRTM 90m and GIS: an example in "Alta Guajira" peninsula, Colombia (2018)
The present research investigates the preferential orientations of morphological features and its relationship with the spatial orientation of tectonic structures in the 'Alta Guajira' peninsula. An SRTM DEM of 90m-resolution data was used to automatically extract geological lineaments and drainage network, which were mapped with the use of GIS techniques. Morphotectonic features were analyzed through the frequency of azimuth and length density distributions. Tectonic controls of the Caribbean plate over the zone were evaluated using previous geological studies of the zone, so the geological map from the SGC (Colombian Geological Service) was used for the terrain analysis. In the same way, a geometrical and oriented azimuth comparison between the automated extracted lineaments and the fault system reported by the SGC were done showing that the major structural trends over the area are N-S and NE-SW. Streams over the surface are divergent and show various anomalies when they transect faults and lineaments, so an orientation analysis of streams were done showing that the preferred azimuth trends for the streams are similar to the result obtained for the lineaments. This was corroborated with an orientation analysis done for the extracted rivers from the SGC geological map. The similarity in the orientation patterns of lineaments and drainage systems highlights the control exerted by geomorphological features. A temporal evolution of the lineament trend through the geological time was done dividing the lineaments into five groups based on the main age of host rocks outcropping in the zone. Lineament trends over the geological time show the evolution of the Caribbean plate since the Cretaceous, highlighting the NE-SW direction motion that the plate has been suffered since then.